(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article develops and substantiates an educational model aimed at developing students’ speech communication system based on associative thinking. The structure of the model consists of goal-oriented, motivational, content-oriented, process-activity and result-evaluation blocks, and is based on the integration of associative, communicative, creative and reflexive components. The results of the research conducted on this basis showed that the developed model significantly developed students’ speech activity, vocabulary, logical speech construction and free communication skills.